(untitled) (CIPEEX, 2025)
This study examines the omission to advise defendants of their right to remain silent— a constitutional and conventional safeguard— and its impact on the validity of procedural acts. It is a doctrinal and case-law review aimed at systematizing criteria for recognizing (or rejecting) relative nullity when the warning is missing. The aim is to set practical parameters for assessing prejudice and curing defects, reconciling the privilege against self-incrimination with procedural effectiveness. The method consisted of analyzing scholarship and precedents that tie Code of Criminal Procedure article 563 (pas de nullité sans grief) to the requirement of concrete harm to the defense, as well as the risk of undue self-incrimination during un-warned examinations. The findings show that nullity is not automatic: it hinges on specific proof of prejudice and may be mitigated by measures such as reopening questioning or disregarding tainted statements; assessment should consider whether the defendant would have remained silent and whether that choice could have affected defense strategy. The conclusion is that lack of warning constitutes relative nullity subject to proof of prejudice, while upholding decisions only where adversarial proceedings and the right to defense remain intact.